Study creativity with diverse social skills to support the learning process in future education - Hadi Suryanto; Sarah Warring; RR. Sri Kartikowati; Widdy HF Rorimpandey; Wawan Gunawan (Journal of diversity in learning (JDIL), 2021)
The characteristics of learners should be a serious concern in the learning process, these characteristics determine the success of the learning process in the classroom. These characteristics are influenced by social skills that are internally individual skills in behaving. Social skills that support the learning process if managed properly will improve the creative process well. Social skills through contact and communication, sympathy and empathy; compromise and cooperation, problem solving, mutual respect,, mutual respect for opinions make the learning atmosphere more interesting and effective that engages them to actively participate in fun learning.